Impairment in recognition of emotional facial expressions in Alzheimer's disease is represented by EEG theta and alpha responses - Güntekin, Bahar; Hano?lu, Lütfü; Aktürk, Tuba; Ruşen, Ece; Yıldırım, Ebru; Yener, Görsev (Blackwell Publishing Inc., 2019)
Behavioral studies have shown that the recognition of facial expressions may be impaired in patients with Alzheimer's disease (AD). The identification and recognition of a facial expression might be represented by event-related brain oscillations. The present study aims to analyze EEG event-related oscillations and determine the electrophysiological indicators of impaired facial expression recognition in AD patients. EEGs of 30 healthy controls and 30 AD patients were recorded during their perception of three different facial expressions (angry, happy, neutral). Event-related power spectrum and phase locking were analyzed in the theta (4?7) and alpha (8?13 Hz) frequency bands with the EEGLAB open toolbox. There was a significant facial Expression × Group interaction (p < 0.05) for the theta power spectrum; the healthy control group had higher theta power than the AD group during the perception of angry facial expressions (p < 0.05). There was a significant hemisphere difference between the two groups (p < 0.05). There was a right hemisphere alpha power dominance in healthy subjects. However, AD patients did not have this alpha power asymmetry. The present study, for the first time in the literature, presents the electrophysiological indicators of impaired recognition of facial expression in AD patients. The current study could be a basis for future studies that will analyze emotional processing in different kinds of dementia patients, and this study may have provided indicators of electrophysiological correlates of behavioral problems observed in clinical practice.
Keywords: Alpha; Alzheimer's Disease; EEG; Event-Related Oscillations; Facial Expression; Theta